2018
DOI: 10.1016/j.biopsych.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Midline Theta Power and Connectivity During Proactive Cognitive Control in Schizophrenia

Abstract: This study suggests that low-frequency midline theta activity is selectively disrupted during proactive cognitive control in SPs. The disrupted midline theta activity may reflect a failure of SPs to proactively recruit cognitive control processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 82 publications
1
40
0
Order By: Relevance
“…This deficit in inhibitory functioning has been related to delayed maturational processing, consistent with studies in healthy children that show that younger children have a poorer performance than older ones on this type of task (Yong-Liang et al, 2000;Durston et al, 2003;Spronk et al, 2008). Interestingly, recent reports have indicated that impaired proactive cognitive control is also present in other pathologies 1 https://neurosynth.org such as schizophrenia and depression in which these alterations crucially impact the quality of life of these patients (Billeke and Aboitiz, 2013;Billeke et al, 2013a;Solomon et al, 2014;Ryman et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This deficit in inhibitory functioning has been related to delayed maturational processing, consistent with studies in healthy children that show that younger children have a poorer performance than older ones on this type of task (Yong-Liang et al, 2000;Durston et al, 2003;Spronk et al, 2008). Interestingly, recent reports have indicated that impaired proactive cognitive control is also present in other pathologies 1 https://neurosynth.org such as schizophrenia and depression in which these alterations crucially impact the quality of life of these patients (Billeke and Aboitiz, 2013;Billeke et al, 2013a;Solomon et al, 2014;Ryman et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…This indicates that TD children, as opposed to children with ADHD, had significantly increased P3a amplitude with longer sequences of preceding Go trials. Since recent reports have shown modulations in a lower oscillatory activity such as delta and theta during the processing of contextual sequence information and proactive cognitive control during inhibition (Harper et al, 2016;Ryman et al, 2018), we tested for time-frequency modulations in our subjects. We calculated the single-trial wavelet transform (−0.5 to 1-s post-stimulus onset) for each subject and modeled the power of the signal using Nogo stimuli, number of preceding Go stimuli and if the preceding trial was an error as regressors (see ''Materials and Methods'' section for more details).…”
Section: Electrophysiological Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) Frontal midline theta power is enhanced during the need for control, whereas mediolateral theta phase synchrony is proposed to reflect the communication of this need to lateral frontal areas (Cavanagh & Frank, ). (b) Different psychiatric and neurological diseases characterized by frontal dysfunction have different patterns of theta band dynamics; 1 Cavanagh, Meyer, et al (); 2 Singh, Pirio Richardson, Narayanan, and Cavanagh (); 3 Ryman et al (). (c) Using features identified in the studies in (b), receiver operating characteristic (isosensitivity) plots can be created to determine the classification success against a control group.…”
Section: Electrophysiology As a Hub For The Neural Sciencesmentioning
confidence: 99%